PENGARUH MODIFIKASI KH2PO4, NH4NO3 DAN SUKROSA TERHADAP PERTUMBUHAN TUNAS SERTA PEMBENTUKAN UMBI MIKRO TAKA (TACCA LEONTOPETALOIDES) SECARA IN VITRO - Rudiyanto, Rudiyanto; Hapsari, Betalini Widhi; Ermayanti, Tri Muji (JURNAL BIOLOGI INDONESIA, 2018)
ABSTRACTPolynesian arrowroot (Tacca leontopetaloides (L.) Kuntze), which is one of the bulbous herbaceous plants,have high nutritional value. Modification of macro nutrients by reducing nitrogen content and increasingphosphorus on the medium gave affects on shoot growth and initiated micro tuber formation on in vitrocultures. The aim of this research was to determine the effect of modified macro nutrients in combination withthe increase in sucrose concentrations on shoot growth and micro tuber formation of T. leontopetaloides. Theexperimental design was factorial completely randomized design.The factors tested were modifications of MSmacro nutrients that were. M1 (170 mg/l KH2PO4 and 1650 mg/l NH4NO3; normal, control treatment); M2 (340mg/l KH2PO4 and 825 mg/l NH4NO3); and M3 (680 mg/l KH2PO4 and 412.5 mg/l NH4NO3 in combinationwith 30 (S1) (control treatment), 40 (S2), 50 (S3) and 60 g/l of sucrose (S4). The variables tested were shootheight, number of leaves, number of roots and number of micro tuber which were observed weekly at 0-8weeks after culturing. The results showed that the modification of macro nutrient in combination with sucroseconcentration had significant effect on shoot height, number of leaves and number of roots but not significanton the number of tubers. The highest shoots were found in M1S3 treatment, the highest number of leaves wasin M1S1 and M1S3 treatment and the highest number of roots was in M1S4 treatment. The number of tubersnot significantly different between the treatments tested.Keywords: in vitro, KH2PO4, microtuber, NH4NO3, sucrose, Tacca leontopetaloides